The Role Of English In The Uzbek National Curriculum: A Critical Analysis Of Language Policy And Globalization - Shokhrukh Toshkinboev; Abdullaev Khayotillo (Periodica Journal, 2025)
This paper provides an in-depth exploration of the role of the English language within Uzbekistan’s national curriculum, examining how language policy intersects with broader processes of globalization. It traces the historical trajectory of English education since independence, analyzes the ideological underpinnings of language reforms, and investigates the practical implications of English as a medium for modernity, economic integration, and cultural identity formation. Drawing on educational policy documents, global frameworks, and sociolinguistic theory, the study presents a critical assessment of how English functions both as a tool of empowerment and a vehicle of soft power in post-Soviet Uzbekistan
Keywords: Language policy; English education; national curriculum; globalization